Effects of polysemy in lexical decision and naming: an alternative to lexical access accounts. - Hino, Yasushi; Lupker, Stephen J. (Journal of Experimental Psychology. Human Perception & Performance, 1996)
The effects of polysemy (number of meanings) and word frequency were examined in lexical decision and naming tasks. Polysemy effects were observed in both tasks. In the lexical decision task, high- and low-frequency words produced identical polysemy effects. In the naming task, however, polysemy interacted with frequency, with polysemy effects being limited to low-frequency words. When degraded stimuli were used in both tasks, the interaction appeared not only in naming but also in lexical decision. Because stimulus degradation also produced an effect of spelling-sound regularity in the lexical decision task, the different relationships between polysemy and frequency appear to be due to whether responding was based primarily on orthographic or phonological codes. As such, the effects of polysemy seem to be due to the nature of task-specific processes. An explanation in terms of M.S. Seidenberg and J.L. McClelland's (1989) and D.C. Plaut and J.L. McClelland's (1993) parallel distributed processing models is proposed. Reprinted by permission of the publisher.